The Construction of Gender Relations in Alternative Media: Cases in Online Media at Magdalene.co and Konde.co - Eny Susilowati; Rhesa Zuhriya Briyan Pratiwi; Ulfa Fauzia Argestya (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2023)
Domestic violence is rising during the pandemic, especially concerning the impact on constructing public opinion regarding the arrangement of women's social roles in the domestic scope (domestication). This research aims to describe the construction of gender relations represented by alternative online media, Magdalane.co, and Konde.co. The research method is descriptive qualitative, with data collection techniques by documentation of texts in the alternative media. The data analysis technique uses Sara Mills' theory about critical discourse. This research's result provides an overview of alternative media perspectives that focus on angles on the subject of the story. Both media deliver a narrative issue with a slightly different ‘sense’ of description. First, Magdalene.co and Konde.co dare to express their disapproval of discrimination among gender. Second, alternative media can break society's stereotypes and actively voice gender equality for men and women.